KEHIDUPAN BERPASANGAN DI PRANCIS DAN PERGESERAN NILAI SOSIAL - Rahmanda, Febriliani; Miranda, Airin (Multikultura, 2026)
This article discusses how legal discourse related to PACS in France reflects and shapes social norms and values that develop in society, particularly in relation to the existence of the mariage pour tous law which was passed fourteen years after the PACS was passed. Both laws were passed by the French government aimed at heterosexual and homosexual couples in order to create equal rights for its citizens. The purpose of this study is to show PACS in France and its relationship to changing social norms, particularly after the passage of the mariage pour tous law in 2013. The theory used in this study is the Critical Discourse Analysis theory by Norman Fairclough which is divided into three dimensions, namely the textual dimension, the discourse dimension and the socio-cultural dimension. In addition, this study uses the concept of individualization by François de Singly. The data used are PACS law number 99-944 dated November 15, 1999 and the official government website. The results of this study indicate that the presence of mariage pour tous which is considered as the answer to the acceptance of all types of couples, both heterosexual and homosexual couples, in fact, the individual, economic, and flexibility values in PACS are still an option for couples who live together today, especially for those who live in big cities, college graduates, and young couples.